Enhanced hydrogen evolution from water splitting based on ZnO nanosheet/CdS nanoparticle heterostructures. Issue 48 (6th September 2019) - Wang, Yinwei; Ping, Hang; Tan, Tiening; Wang, Wenxuan; Ma, Peiyan; Xie, Hao
Abstract : ZnO nanosheet/CdS nanoparticle heterostructures were synthesized by a mild wet chemical reaction and displayed high hydrogen production with free Pt loading under visible light radiation. Abstract : As environmental and energy problems have worsened worldwide, research for developing renewable energy has become urgent. Presently, the primary focus of such research is directed towards the photocatalytic decomposition of water to produce hydrogen as an energy source. Herein, ZnO nanosheet/CdS nanoparticle heterostructures were synthesized by a mild wet chemical reaction and displayed a high photocatalytic efficiency (1040 μmol g −1 h −1 ) without Pt loading under visible light radiation. The structure was prepared by first constructing two-dimensional nanocrystalline ZnO flowers and then loading CdS nanoparticles onto the nanocrystals. Results show that this structure can facilitate the separation of photogenerated electrons and holes and improve the photocatalytic efficiency and stability of the materials in the photocatalytic decomposition of water. By changing different experimental conditions to prepare a variety of samples and test their properties, we can analyze the optimal parameters for the preparation of this material.